Situational diagnosis and proposal of a zoosanitary monitoring program for the Sauce Grande sector of El Angolo game reserve, Piura – Peru - Muñoz Durán, Karina (2021)
El Angolo Game Reserve was created in 1975 to promote the rational use of authorized wild fauna and flora, in particular species intended for sport hunting such as the white-tailed deer, but it has few publications on health issues. There are only two reports of deer mortality events, one occurred in 1976, of which the cause of death could not be known, and a second event in 2011, where dozens of dead deer were reported and necrobacillosis was confirmed as the cause of death. Therefore, the objective of this study is to have a situational diagnosis of some infectious and parasitic diseases, and to propose a zoosanitary monitoring program for the white-tailed deer and domestic ungulates of the Sauce Grande sector of the El Angolo Game Reserve, Piura that allows knowing which parasitic and infectious agents are circulating and serves to establish preventive and control measures to avoid or reduce the occurrence of mortality events.